ANALYSIS OF JOB SATISFACTION OF TEA PLANTATION WORKERS OF KERALA USING A STRUCTURAL EQUATION MODELLING APPROACH - ARYA V. CHANDRAN*, DIGVIJAY SINGH DHAKRE, DEBASIS BHATTACHARYA; KADER ALI SARKAR (The Journal of Research ANGRAU, 2023)
The study aimed to identify the effects of different factors on job satisfaction of tea plantation workers. Like any other industry, the satisfaction of labours have significant role in the development of tea industry. The tea plantation workers in India are covered by Plantation Labour Act (PLA) 1951, which prescribes the standards of working and living conditions. The data regarding the satisfaction of different factors including working and living conditions were collected from 400 respondents of Kerala through structured interview schedule. To determine the influence of various factors influencing job satisfaction, appropriate statistical approaches, such as Exploratory Factor Analysis (EFA) and Structural Equation Modelling (SEM) technologies, were employed.The goodness of fit for the fitted model was checked by fitness indices. Using SEM, it was observed that the company’s provision of facilities such housing, water, electricity, protective clothing, health care, and recreational activities has an effect on the job satisfaction of plantation workers.